Models for exploring partnership: Introducing sparqs’ student partnership staircase as a reflective tool for staff and students - Varwell, Simon (International Journal for Students as Partners, 2021)
A useful way of exploring partnership between staff and students is through visual representations of partnership, where the concept sits alongside other ideas in scales or diagrams. They enable comparison, benchmarking and reflection in a way that is facilitative rather than instructional. Many such tools approach partnership in different ways and can be used in various contexts by staff and students. This article explores some of those tools, and introduces sparqs’ student partnership staircase, a simple tool which places partnership at the top of a four-step scale, prompting conversations about the role that students can and should play in shaping quality and how staff and institutions can enable this. Consideration is given to how the staircase can be used to create mutual learning spaces for staff and students and prompt shared understandings about partnership in quality.